2013
DOI: 10.1111/jvh.12215
|View full text |Cite
|
Sign up to set email alerts
|

Association of a microRNA‐323b polymorphism with the persistence of hepatitis B virus infection by the enhancement of viral replication

Abstract: Recent studies have shown that some mammalian microRNAs (miRNAs) play a role in antiviral defence. However, little is known about the role of miRNA-323b in hepatitis B virus (HBV)-host interaction. We explored whether single nucleotide polymorphism (SNP) of miRNA-323b affects HBV replication in a Korean HBV cohort. Genotyping was performed in a total of 1439 subjects composed of 404 spontaneously recovered (SR) subjects as normal controls and 1035 chronic carriers (CC) of HBV who were further classified into 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…miRNA regulation has been described in a wide range of leukocytes and in the innate immune responses of non-leukocytes ( 12 , 34 , 63 71 ). Indeed, single nucleotide polymorphisms in miRNA loci have been associated with susceptibility to leprosy and infection outcome in human cytomegalovirus (hCMV) and hepatitis B infection ( 72 76 ). Although confirming the functional nature of such associations is difficult, the findings of such studies are in keeping with the important role of miRNAs in immunity and provide some evidence that person to person variation in susceptibility to infection could be governed by polymorphism in miRNA genes, at least for certain pathogens.…”
Section: Micrornas Mediate Innate and Adaptive Immunitymentioning
confidence: 99%
“…miRNA regulation has been described in a wide range of leukocytes and in the innate immune responses of non-leukocytes ( 12 , 34 , 63 71 ). Indeed, single nucleotide polymorphisms in miRNA loci have been associated with susceptibility to leprosy and infection outcome in human cytomegalovirus (hCMV) and hepatitis B infection ( 72 76 ). Although confirming the functional nature of such associations is difficult, the findings of such studies are in keeping with the important role of miRNAs in immunity and provide some evidence that person to person variation in susceptibility to infection could be governed by polymorphism in miRNA genes, at least for certain pathogens.…”
Section: Micrornas Mediate Innate and Adaptive Immunitymentioning
confidence: 99%
“…MiR‐323b‐5p was previously named miR‐453(Altuvia et al, ; Landgraf et al, ), but appears to be processed from the same hairpin. Recently published articles have demonstrated that rs56103835 in miR‐323b was associated with the persistence of hepatitis B virus infection by the enhancement of viral replication (Yu et al, ). Polymorphisms of protein coding genes in the hsa‐miR‐323b binding site have been identified to be associated with many diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published report showed that rs56103835 C>T in the pre‐miRNA region of miRNA‐323b was significantly associated with persistence of HBV by the enhancement of HBV replication (Yu et al, ). And it will be an interesting question whether SNPs in pre‐miR‐323b is related with other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Still considering Korean patients, Yu et al ( 80 ) evaluated the miR-323b A/C/T SNP (rs56103835) on HBV replication and clinical course of infection. In that study, miR-323b rs56103835 was associated with persistent infection and was hypothesized as a factor which facilitates chronic HBV infection.…”
Section: Viral Infections and Polymorphic Variants That Affect Mirnasmentioning
confidence: 99%